2012
DOI: 10.1016/j.reprotox.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine rescues ketamine-induced attenuated heart rate and MAPK (ERK) activity in zebrafish embryos

Abstract: Ketamine, an antagonist of the N-methyl-D-aspartate (NMDA)-type glutamate receptors, is a pediatric anesthetic. Ketamine has been shown to be neurotoxic and cardiotoxic in mammals. Here, we show that after 2 h of exposure, 5 mM ketamine significantly reduced heart rate in 26 h old zebrafish embryos. In 52 h old embryos, 1 mM ketamine was effective after 2 h and 0.5 mM ketamine at 20 h of exposure. Ketamine also induced significant reductions in activated MAPK (ERK) levels. Treatment of the embryos with the ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 62 publications
5
81
0
Order By: Relevance
“…The rationale behind this experiment was based on the notion that being younger by 20 h than the 48 hpf embryos, the skin of the 28 hpf embryos will be less complex and more permeable to ketamine, thus facilitating enhanced diffusion. The dose and duration were selected on the basis of our previous report on ketamine-induced cardiotoxicity in zebrafish embryos (Kanungo et al, 2012). In our studies, although ketamine dose was high in the embryo water, the real exposure turned out to be significantly lower; at 2.0 mM ketamine dose, each embryo only accumulated 8.4 μM.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The rationale behind this experiment was based on the notion that being younger by 20 h than the 48 hpf embryos, the skin of the 28 hpf embryos will be less complex and more permeable to ketamine, thus facilitating enhanced diffusion. The dose and duration were selected on the basis of our previous report on ketamine-induced cardiotoxicity in zebrafish embryos (Kanungo et al, 2012). In our studies, although ketamine dose was high in the embryo water, the real exposure turned out to be significantly lower; at 2.0 mM ketamine dose, each embryo only accumulated 8.4 μM.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, in another study we also showed that acetyl L-carnitine counteracts ketamine's negative effects on heart rate and ERK (MAPK) activity in zebrafish embryos (Kanungo et al, 2012). In order to quantitate the effect of ketamine on motor neurons in vivo, hb9:green fluorescent protein (hb9:GFP) transgenic zebrafish embryos were used, in which the promoter of the transcription factor hb9 that is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004), drives GFP expression specifically in motor neurons (Flanagan-Steet et al, 2005;Nakano et al, 2005).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations